Upaya Meningkatkan Kompetensi Guru Kelas dalam Proses Pembelajaran Berdasarkan Kurikulum 2013 Melalui Supervisi Akademik di SD Negeri 45 Mataram - Purnamaraya, Siti (Jurnal Paedagogy, 2019)
The purpose of this study was to determine the effectiveness of the implementation of academic supervision in an effort to improve the competence of Class Teachers in classroom learning. This research method uses a school action research conducted during three cycles, each cycle of activities there are four stages, namely planning, implementation, observation, and reflection. The results of this study indicate that; 1) the results of observations by the school principal and teacher observations during the mentoring process have received an average score of> 4.0, and 2) the final result> 85% of the total number of mentoring participants received an average grade of> 80.00 (good category). The results of the study in the first cycle of observation of the average School Principal (2.90), the observation of the average teacher (2.67) and the academic supervision results of the average grade teacher (62.86). In cycle II the observations of the average headmaster (3.40), the observation of the average teacher (3.50) and the results of academic supervision at the target grade point average (78.73). Cycle III observations of average principals (4.60), observations of average teachers (4.67) and academic supervision results in the average target value (86.49) Indicators of success have been achieved, research is declared successful and terminated in cycle III. The conclusion of this research is that in the third cycle it shows an increase in teacher competence in the learning process in class.